2022
DOI: 10.1101/2022.11.24.517835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organization, genomic targeting and assembly of three distinct SWI/SNF chromatin remodeling complexes inArabidopsis

Abstract: Switch defective/sucrose non-fermentable (SWI/SNF) complexes are evolutionarily conserved multi-subunit machines that play vital roles in chromatin architecture regulation for modulating gene expression via sliding or ejection of nucleosomes in eukaryotes. In plants, perturbations of SWI/SNF subunits often result in severe developmental disorders. However, the subunit composition, pathways of assembly, and genomic targeting of the plant SWI/SNF complexes remain undefined. Here, we reveal that Arabidopsis SWI/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Our data is also consistent with LFR being a component of a MINU1/2 ATPase‐containing SWI/SNF complex (Diego‐Martin et al., 2022), although in this case, the interaction between LFR and MINU1/2 would be indirect. During the review of our manuscript, two recent studies reported that LFR is involved in both the SAS and MAS complex (SYD‐ and MINU1/2‐associated SWI/SNF complexes) (Fu et al., 2023; Guo et al., 2022), which serves as supports of our work. Indeed, multiple SAS or MAS components were specifically co‐purified with LFR‐3FLAG in our IP‐MS assays (Figure 1c).…”
Section: Discussionsupporting
confidence: 73%
“…Our data is also consistent with LFR being a component of a MINU1/2 ATPase‐containing SWI/SNF complex (Diego‐Martin et al., 2022), although in this case, the interaction between LFR and MINU1/2 would be indirect. During the review of our manuscript, two recent studies reported that LFR is involved in both the SAS and MAS complex (SYD‐ and MINU1/2‐associated SWI/SNF complexes) (Fu et al., 2023; Guo et al., 2022), which serves as supports of our work. Indeed, multiple SAS or MAS components were specifically co‐purified with LFR‐3FLAG in our IP‐MS assays (Figure 1c).…”
Section: Discussionsupporting
confidence: 73%
“…4B; Supplemental Dataset 5). Previous studies have indicated that, in seedlings, BAS and SAS share the majority of their binding peaks, while most of the binding peaks of MAS are different from those of BAS and SAS (Guo et al, 2022; Fu et al, 2023). The overlapping patterns of BAS, SAS, and MAS peaks in inflorescences were similar to those in seedlings (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 98%
“…SWI/SNF complexes play crucial roles in the regulation of diverse developmental processes in both metazoans and plants. Recent studies have illustrated the functional variations among the three Arabidopsis SWI/SNF complexes: BAS, SAS, and MAS (Guo et al, 2022; Fu et al, 2023). However, the precise mechanisms by which these complexes exert specific functions during different developmental stages remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active regulatory DNA regions require continuous chromatin remodeling activity of SWI/SNF complexes; therefore, their activities must be tightly regulated to ensure fidelity and plasticity of genomic processes (39,40). In Arabidopsis, three subclasses of SWI/SNF chromatin remodeling complexes were identified: BRM-associated SWI/SNF complexes (BAS), SPLAYEDassociated SWI/SNF complexes (SAS), and MINUSCULE-associated SWI/SNF complexes (MAS) (41,42). However, the molecular mechanisms responsible for the precise localization of SWI/SNF chromatin remodeling complexes to specific genomic loci, therefore ensuring their proper activity during the intricate processes of growth and development, remain obscure.…”
Section: Introductionmentioning
confidence: 99%